Peran Locus of Control terhadap Kinerja Karyawan melalui Kepuasan Kerja pada Karyawan PT. Ilham Hasil Mandiri Kabupaten Sidoarjo - Prayoga Putra Wardhana (Jurnal Ilmu Manajemen, 2021)
The study aims to determine and analyze the effect of Locus of control on employee performance through job satisfaction. Research object at PT. Ilham Hasil Mandiri Sidoarjo City, with a sample of 44 of 51 employees, this research is used as a Structural Equation Model (SEM) with the assistance of Smart Pls 3.0 software as the statistical analysis. The results of this study indicate that the Locus of control has a positive and significant effect on employee performance, the Locus of control has a significant negative effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, the Locus of control has a positive and significant effect on employee performance through job satisfaction